THE USE OF BASIC DRUGS IN THE TREATMENT OF BRONCHIAL ASTHMA IN CHILDREN - Z. N. Sherova, K.Sh. Shaabidova (Galaxy International Interdisciplinary Research Journal, 2023)
Bronchial asthma is a chronic disease that causes a significant limitation of life, a decrease in social and physical activity. Constant attention to the problem of asthma is also due to the fact that with insufficiently effective treatment, frequent exacerbations of the disease, the quality of life of patients decreases, limiting their vital activity. Severe forms of bronchial asthma are accompanied by impaired functions not only of the respiratory organs, but also of other body systems [13-14]. Disability develops in 7% of officially registered children with bronchial asthma.